2001
DOI: 10.1093/geront/41.4.462
|View full text |Cite
|
Sign up to set email alerts
|

The Stress Process of Family Caregiving in Institutional Settings

Abstract: These results suggest that caregiver depression is closely linked to how well both the resident and caregiver adjust to the nursing home environment. Results also indicate that by broadening the SPM to include stressors common to the nursing home experience, researchers will be able to understand more clearly the specific components of the stress process that may lead to depression in family caregivers of persons living in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
1
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(157 citation statements)
references
References 33 publications
9
141
1
6
Order By: Relevance
“…Numerous studies support the need for improved relations and lament the lack of a truly collaborative approach to care (Bowers, 1988;Friedemann et al, 1997;Laitinen & Isola, 1996; and see Janzen, 2001 for a review). Other research has found that negative interactions with staff have a negative influence on resident and caregiver outcomes (Whitlatch et al, 2001). These results go a step further to demonstrate that caregivers who report problematic relationships with staff also visit less frequently.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Numerous studies support the need for improved relations and lament the lack of a truly collaborative approach to care (Bowers, 1988;Friedemann et al, 1997;Laitinen & Isola, 1996; and see Janzen, 2001 for a review). Other research has found that negative interactions with staff have a negative influence on resident and caregiver outcomes (Whitlatch et al, 2001). These results go a step further to demonstrate that caregivers who report problematic relationships with staff also visit less frequently.…”
Section: Discussionsupporting
confidence: 57%
“…Residents were typical in terms of length of stay, age, and Medicaid funding (Bitzan & Kruzich, 1990;Dempsey & Pruchno, 1993;Ross, Carswell, & Dalziel, 2001;Tornatore & Grant, 2002;Whitlatch et al, 2001). Although MMSE scores ranged from 0 to 26, caution should be used when these results are applied to caregivers of cognitively intact NH residents, as the barriers and difficulties they face may differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these support systems might at least temporarily overshadow the caregiver burden. Furthermore, it is known that caregivers continuing home care feel as burdened as their colleagues deciding to place their care needing relative (Lieberman and Kramer, 1991;Gold et al, 1995;Whitlatch et al, 2001). Beside, caregivers' feelings of control are changing during the period of home care but do not influence the final risk of definitive institutionalization (Vernooij-Dassen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…15 More recent studies conclude that NHA results in guilt, anger, anxiety, and depression for dementia caregivers, although others suggest that NHA does little to influence the trajectories of stress or negative mental health prior to and after institutionalization. 13,14 [16][17][18][19][20] Additional descriptive research focused on the new challenges that institutionalization pose for families, such as the negative interactions between family caregivers and staff as control of care is shifted to the facility and the family member is left with an ambiguous care role. 11,16,18 Parallel to descriptive analyses of dementia caregiving and institutionalization, a series of clinical efforts have sought to alleviate the psychological, emotional, and physiological distress that can occur as a function of intensive family care provision.…”
Section: Introductionmentioning
confidence: 99%